2004
DOI: 10.1007/s00122-004-1658-0
|View full text |Cite
|
Sign up to set email alerts
|

A microsatellite map of white clover

Abstract: The white clover ( Trifolium repens) nuclear genome (n = 2x = 16) is an important yet under-characterised genetic environment. We have developed simple sequence repeat (SSR) genetic markers for the white clover genome by mining an expressed sequence tag (EST) database and by isolation from enriched genomic libraries. A total of 2,086 EST-derived SSRs (EST-SSRs) were identified among 26,480 database accessions. Evaluation of 792 EST-SSR primer pairs resulted in 566 usable EST-SSRs. Of these, 335 polymorphic EST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 63 publications
5
118
4
Order By: Relevance
“…Here we have identified the gene that is likely to underlie the Ac/ac cyanogenic glucoside polymorphism; we have found that, like Li/li, this component of the cyanogenesis polymorphism apparently arises through a gene presence/absence polymorphism. With recent advances in the development of genetic and genomic tools for white clover (e.g., Barrett et al 2004;Cogan et al 2007), this species may prove a useful resource for further studies on the molecular genetics of adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have identified the gene that is likely to underlie the Ac/ac cyanogenic glucoside polymorphism; we have found that, like Li/li, this component of the cyanogenesis polymorphism apparently arises through a gene presence/absence polymorphism. With recent advances in the development of genetic and genomic tools for white clover (e.g., Barrett et al 2004;Cogan et al 2007), this species may prove a useful resource for further studies on the molecular genetics of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a perennial and an insectpollinated, obligate outcrosser; plants also spread vegetatively by stolons. Chromosome number and genetic map data indicate that white clover is an allotetraploid (e.g., Barrett et al 2004). While Ac and Li have not been mapped, both cyanogenesis genes are believed to be present in only one of the two parental genomes (e.g., Williams and Williamson 2001); this suggests that the species originated through the hybridization of a cyanogenic and an acyanogenic Trifolium species (Williams and Williamson 2001;Badr et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The location of the SI locus was described by Casey et al [14] and utilised a characterised BAC library for white clover with partial BAC end sequencing reported by Febrer et al [14]. Genetic maps in white clover have been reported by several groups [12,[15][16][17]. They were all based on a mixture of SSR and AFLP markers [12], or exclusively SSR markers.…”
Section: Germplasm and Breedingmentioning
confidence: 99%
“…In choosing the crossing parents, it is recommended that, they should be different in the traits of interest in order to facilitate linkage mapping and segregation analysis (Young, 1994). However, when using mapping populations based on highly heterozygous parents, differences in the trait of interest between the parents is not essential, because many of the genes underpinning the trait still segregate in the population (Barrett et al, 2004). There are several methods for generating a mapping population, but the choice depends on the pollination pattern of the plant species.…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of the former breeding method is that, it minimizes the risk of inbreeding depression and segregation distortion in the mapping population, both of which can significantly reduce the power and utility of a genome map (Faville et al, 2003). The successful use of a double heterozygous (or double-pseudotestcross) strategy in open pollinated species has been reported in linkage mapping for perennial ryegrass (Faville et al, 2004), white clover (Barrett et al, 2004) Eucalyptus (Grattapaglia and Sederoff, 1994) and asparagus (Lewis and Sink, 1996).…”
Section: Introductionmentioning
confidence: 99%